Outcomes in neonates with respiratory distress syndrome using SAANS NIV - Hailu, Michael T.; Workagegnehu, Kaleab D.; Manoj, Adarsh (International Journal Of Community Medicine And Public Health, 2022)
Background: In low-and-middle income countries (LMICs), neonatal mortality is still unacceptably high compared to developed nations. Respiratory distress syndrome (RDS) is one of the major contributors to high mortality rates in this population. This study was conducted to analyze the effects of Saans non-invasive ventilation (NIV), an infrastructure-independent continuous positive airway pressure (CPAP) and resuscitation device, on neonatal mortality and cost compared to current practices. Methods: This single-center, prospective, observational analytical study was to determine the efficacy of Saans NIV in delivering CPAP and resuscitation therapy to neonates diagnosed with RDS. Results: An 82% success rate was recorded while using Saans NIV for CPAP and resuscitation therapy in this study, which was far superior to the global average. This also means that 82% of the patients included in this study avoided invasive mechanical ventilation. After a cost analysis, we concluded that invasive mechanical ventilation would cost $3478 USD for treatment vs. just $155 USD for patients treated with traditional CPAP therapy. Conclusions: Infrastructure-independent devices such as Saans NIV are game-changers in LMICs. Saans NIV makes CPAP and safe resuscitation therapy available in resource-constrained settings and during transport. This study showcases that Saans NIV can significantly reduce the need for invasive mechanical ventilation and the costs associated with treating neonates.